A flexible islanding identification technique for PV based grid-tied systems - Sarojam, Praveen Raj Rajaswamy; Savier, Joseph Sarojini (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The phenomenon of islanding, which occurs in grid integrated distributed generators (DGs), poses significant challenges and potential risks for customers, utility providers, and operational personnel. Detecting islanding quickly and accurately is crucial. The issues related to the conventional islanding methods paved the way in developing a hybrid islanding identification scheme. The developed method achieves accurate results within a reduced time span of 30 ms. The hybrid technique combines the passive method of sliding window based moving average (SWMA) for faster detection and the active method of asymmetrical bilateral reactive power perturbation (ABRPP) for improved precision. The developed hybrid method is simulated and tested using MATLAB/Simulink 2023a. It undergoes testing under various load conditions, including small and large power mismatches between DG generation and local load demand, as well as different load quality factors (QF). Additionally, the hybrid algorithm demonstrates no nuisance tripping when subjected to different load switching conditions such as capacitor switching, motor load switching, and nonlinear load switching. A comparison with existing islanding detection methods confirms the accuracy and speed of the proposed method in identifying islanding conditions.